2009
DOI: 10.1203/pdr.0b013e3181bbdf2b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fish Oil-Based Lipid Emulsion on Serum Triglyceride, Bilirubin, and Albumin Levels in Children With Parenteral Nutrition-Associated Liver Disease

Abstract: Parenteral nutrition is known to cause liver injury in babies. The aim of this study is to investigate the effects of different lipid emulsions on parenteral nutrition-associated cholestasis in infants. In addition, there may be a relationship between the lipid emulsion and triglyceride levels. Furthermore, triglyceride levels may correlate with direct bilirubin and albumin, as markers of liver impairment and nutritional status. Patients with parenteral nutrition-associated cholestasis who were treated with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…No clinically significant bleeding related to Omegaven was noted in any subjects. This safety profile, as well as the reduction in direct bilirubin, is comparable to previous reports [1,2]. Limitations of our study are lack of standard randomization and the fact that lipid loads for soybean oil (Intralipid) were not constant across the study subjects.…”
Section: Resultssupporting
confidence: 86%
“…No clinically significant bleeding related to Omegaven was noted in any subjects. This safety profile, as well as the reduction in direct bilirubin, is comparable to previous reports [1,2]. Limitations of our study are lack of standard randomization and the fact that lipid loads for soybean oil (Intralipid) were not constant across the study subjects.…”
Section: Resultssupporting
confidence: 86%
“…Other factors that may affect the bloodstream clearance of intravenous triglycerides entail enzymatic and nonenzymatic pathways [31,32], diameter of triglyceride droplets of IVLE [33], and the type of triglyceride substrate, i.e., chain length distribution of fatty acids, degree of fatty acid unsaturation and double bond position, and the positional distribution of specific fatty acids within the triacylglyceride molecule [34,35]. In a cohort study, serum triglyceride levels declined more rapidly over time in children receiving fish-oil based IVLE than in those receiving soy-oil based IVLE [14]. The pathways responsible for the clearance of intravenously infused MCT, n-3 fatty acid-rich fish oil, and n-6 fatty acid-rich soybean oil differ considerably [31,32].…”
Section: Tablementioning
confidence: 99%
“…In a prospective study in infants it was shown that the use of IVLE exclusively based on fish, and hence not providing appreciable amounts of phytosterols, was associated with the reversal of IFALD in infants [14]. A meta-analysis addressing the effect of fish oilcontaining IVLE in neonates with IFALD requiring prolonged parenteral nutritional, suggests that these IVLE are effective for treatment but not for prevention of IFALD [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, given the homogeneity of the two groups prior to and after transplantation, we can assume that the variations found in the lipid profile may be due to the lipid emulsions used in PN. This differentiates our study from previous studies based on heterogeneous samples in terms of age and type of pathology [14,15]. …”
Section: Discussionmentioning
confidence: 43%
“…Different studies in infants under one year of age have reported liver alterations after prolonged administration of a soy formula. After replacement of the soy formula with a fish oil formula a decrease was observed in direct serum bilirubin, TG [8,14], total cholesterol, cLDL and VLDL [8], with the subsequent resolution of cholestasis and normalization of the liver function [8,14,18]. This formula has also been linked to a significant increase in serum ω3 LCPUFAS (EPA and DHA), and a decrease in ω6 (AA) [8].…”
Section: Discussionmentioning
confidence: 99%